Pola Interaksi Remaja Perempuan dengan Orang Tua Pasca Perceraian Orang Tua - Nuzulah, Mega Aulya; Listyani, Refti Handini (Paradigma, 2023)
The occurrence of divorce does not always concern the husband and wife but also concerns the child because the divorce will have an impact on determining the status of the child. When the child's interaction with parents will also change after divorce. The child's interaction will also be hampered with the outside world because the child's internal interaction with parents has problems due to divorce. This study focuses on the pattern of interaction of children to parents after divorce, especially to children where usually in this situation girls prefer to limit their socialization with the surrounding environment after what happens in their family. The purpose of this study was to identify the objective conditions of post-divorce adolescent girls and analyze their interaction patterns after parental divorce. This research uses qualitative research methods with the perspective of George Herbert Mead's symbolic interaction theory. The results of this study found that adolescent girls take action to withdraw from their social and family environment due to parental divorce and lack of interaction with parents, especially after divorce. The number of meetings between children and parents decreases after divorce. Where from this makes adolescent girls feel distant from their parents, especially when they enter adolescence where it is a period of self-discovery where they should get special attention from their parents.